2000
DOI: 10.1093/brain/123.4.733
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinations in Parkinson's disease: Prevalence, phenomenology and risk factors

Abstract: Hallucinations, mainly of a visual nature, are considered to affect about one-quarter of patients with Parkinson's disease. They are commonly viewed as a side-effect of antiparkinsonian treatment, but other factors may be involved. The aim of this study was to determine the phenomenology, prevalence and risk factors of hallucinations in Parkinson's disease. Two-hundred and sixteen consecutive patients fulfilling clinical criteria for Parkinson's disease were studied. Demographic and clinical variables were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
780
22
34

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 894 publications
(897 citation statements)
references
References 41 publications
41
780
22
34
Order By: Relevance
“…The lower prevalence rate of hallucinations here reflects the earlier disease‐stage, community‐based nature of our population when compared with other studies showing higher prevalence rates 9, 10…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The lower prevalence rate of hallucinations here reflects the earlier disease‐stage, community‐based nature of our population when compared with other studies showing higher prevalence rates 9, 10…”
Section: Discussioncontrasting
confidence: 53%
“…Misperception of objects in PD10 may be caused by top‐down processes, where patients are primed to see objects more readily, or to impaired object detection. We tested these 2 competing theories using object detection within a complex scene 11…”
Section: Methodsmentioning
confidence: 99%
“…It was once thought that treatment with higher dosages or particular classes (e.g., dopamine agonists) of dopamine replacement therapies was the primary etiology of psychosis in PD [24]. While numerous case series, epidemiological studies, and treatment studies have found psychosis to be related to levodopa [25] and dopamine agonist [26,27] use, several other recent epidemiological studies have not found an association between antiparkinsonian medication and the occurrence of psychosis [6,28,29]. Regardless the exact association between antiparkinsonian medications and psychosis, it is now thought that the etiology of psychosis in PD is multi-factorial, including other risk factors such as increasing age [6], longer duration and greater severity of PD [5,6], executive [30] and other forms of cognitive impairment [5][6][7], visual impairment [5], and increasing severity of depression [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Psychotic symptoms, particularly visual hallucinations and paranoid delusions, occur in up to 40% of patients with Parkinson's disease (PD) who receive dopamine (DA) replacement therapy (Chou et al, 2007;Fenelon et al, 2000;Fernandez et al, 2003: Friedman, 1991, Goetz et al, 2001Weintraub and Stern, 2005;Ravina et al, 2007;Diederich et al, 2009). Psychotic symptoms in PD psychosis (PDP) are a significant cause of distress to patients and their caregivers, and are associated with greater functional impairment, caregiver burden, nursing home placement, and increased mortality (Weintraub and Stern, 2005;Factor et al, 2003).…”
Section: Introductionmentioning
confidence: 99%